Implementasi Digital Marketing Booster Fermentasi Mandiri Dalam Peningkatan Pendapatan Kelompok Tani Lestari II - Sunandes, Aris; Puspitorini, Palupi; Winurdana, Alfan Setya; Pitaloka, Dyah (AJAD : Jurnal Pengabdian kepada Masyarakat, 2024)
The aim of this research is to apply digital marketing of an independent fermentation booster to increase the income of the Sustainable Farmers Group II located in Tegalrejo Village, Selopuro District, Blitar Regency. In general, this group focuses energy and time on developing an independent fermentation booster for their silage. The process of implementing digital marketing with empowerment begins with intensive training in making independent fermentation boosters. Farmers are thoroughly trained in proper fermentation techniques to produce high quality silage. This training not only emphasizes technical skills, but also introduces essential business management concepts. Farmers are taught production planning, quality control, and inventory management to ensure consistency and sustainability in their booster production. They gain skills in brand building, creating engaging content, and leveraging digital analytics to increase the visibility and sales of their self-fermentation boosters with digital marketing. Assistance has been proven to be able to increase income results through making fermentation boosters independently, while the excess from making it becomes added value for resale and is able to provide side income which has results equivalent to the Blitar Regency minimum wage, this is significant in increasing income for farmer groups Lestari II in optimizing their agricultural potential in a sustainable manner.